Pengembangan Model Evaluasi Pembelajalaran Ekonomi Berbasis Artificial Intelligence (AI): Studi Validasi dan Implementasi - Burhan, Misran U; Hasim Hasim (Lembag, 2025)
This study examines the impact of the use of artificial intelligence (AI) in adaptive learning on the learning interests of Generation Z students in higher education. Using a mixed-method approach, the study combined quantitative and qualitative methods to gain a comprehensive understanding. Data were collected from 300 respondents through a survey measuring student engagement and motivation, as well as in-depth interviews to explore their experiences with AI-based learning tools. The results indicate that 75% of students felt more motivated and engaged when using AI-based tools, with significant improvements in their understanding of the material. The study also identified challenges in AI implementation, including concerns over personal data protection, educator readiness, and ethical use of the technology. These findings suggest that AI has significant potential to enhance the learning experience by promoting greater engagement and deeper understanding. However, appropriate regulation, infrastructure, and support are needed to optimize AI’s use in education and address emerging challenges effectively.